Define the formula of ${{a}^{3}}-{{b}^{3}}$.
Answer
Verified
510k+ views
Hint: Here we will derive the formula of $\left( {{a}^{3}}-{{b}^{3}} \right)$ by taking into account the formula of ${{\left( a-b \right)}^{3}}$which is, ${{\left( a-b \right)}^{3}}={{a}^{3}}-{{b}^{3}}-3ab\left( a-b \right)$. Then we will add $3ab\left( a-b \right)$both the sides and simplify this expression to get $\left( {{a}^{3}}-{{b}^{3}} \right)$.
Complete step-by-step answer:
Here we have to define the formula of ${{a}^{3}}-{{b}^{3}}$.
To get the formula of ${{a}^{3}}-{{b}^{3}}$, first of all, we have to derive the formula of ${{\left( a-b \right)}^{3}}$.
We know that ${{\left( a-b \right)}^{3}}=\left( a-b \right)\left( a-b \right)\left( a-b \right)$
By simplifying the RHS of above equation, we get,
$\begin{align}
& {{\left( a-b \right)}^{3}}=\left( a-b \right)\left( {{a}^{2}}-ab-ba+{{b}^{2}} \right) \\
& or\ {{\left( a-b \right)}^{3}}=\left( a-b \right)\left( {{a}^{2}}-2ab+{{b}^{2}} \right) \\
\end{align}$
By further simplifying the RHS of above equation, we get,
${{\left( a-b \right)}^{3}}={{a}^{3}}-2{{a}^{2}}b+{{b}^{2}}a-b{{a}^{2}}+2a{{b}^{2}}-{{b}^{3}}$
Therefore we get, ${{\left( a-b \right)}^{3}}={{a}^{3}}-{{b}^{3}}-3{{a}^{2}}b-3{{b}^{2}}a$.
We can also write the above equation as,
${{\left( a-b \right)}^{3}}={{a}^{3}}-{{b}^{3}}-3ab\left( a-b \right)$
Now by adding $3ab\left( a-b \right)$ on both sides of above equation, we get,
${{\left( a-b \right)}^{3}}+3ab\left( a-b \right)=\left( {{a}^{3}}-{{b}^{3}} \right)-3ab\left( a-b \right)+3ab\left( a-b \right)$
By cancelling the like terms from RHS, we get,
$\begin{align}
& {{\left( a-b \right)}^{3}}+3ab\left( a-b \right)=\left( {{a}^{3}}-{{b}^{3}} \right) \\
& or\ {{a}^{3}}-{{b}^{3}}={{\left( a-b \right)}^{3}}+3ab\left( a-b \right) \\
\end{align}$
By taking out (a - b) common from RHS, we get,
$\Rightarrow {{a}^{3}}-{{b}^{3}}=\left( a-b \right)\left[ {{\left( a-b \right)}^{2}}+3ab \right]$
As we know that ${{\left( a-b \right)}^{2}}={{a}^{2}}+{{b}^{2}}-2ab$, by applying it in above equation, we get,
$\Rightarrow {{a}^{3}}-{{b}^{3}}=\left( a-b \right)\left( {{a}^{2}}+{{b}^{2}}-2ab+3ab \right)$
Therefore we get, ${{a}^{3}}-{{b}^{3}}=\left( a-b \right)\left( {{a}^{2}}+{{b}^{2}}+ab \right)$
Hence we have found the formula for ${{a}^{3}}-{{b}^{3}}$which is equal to $\left( a-b \right)\left( {{a}^{2}}+{{b}^{2}}+ab \right)$.
Note: Here, apart from finding ${{\left( a-b \right)}^{3}}$by multiplying $\left( a-b \right)$ three times, students can directly use the formula of ${{\left( a-b \right)}^{3}}$, that is ${{\left( a-b \right)}^{3}}={{a}^{3}}-{{b}^{3}}-3ab\left( a-b \right)$.
Also students can cross check the formula by taking any value of a and b and satisfying them in formula as follows:
Let us take a = 4 and b = 2.
We have found that, ${{a}^{3}}-{{b}^{3}}=\left( a-b \right)\left( {{a}^{2}}+{{b}^{2}}+ab \right)$
By putting the values of a and b in above equation, we get,
$\Rightarrow {{\left( 4 \right)}^{3}}-{{\left( 2 \right)}^{3}}=\left( 4-2 \right)\left( {{\left( 4 \right)}^{2}}+{{\left( 2 \right)}^{2}}+4\times 2 \right)$
By simplifying the above equation, we get,
$\begin{align}
& \Rightarrow 64-8=\left( 2 \right)\left( 16+4+8 \right) \\
& \Rightarrow 56=2\left( 28 \right) \\
& \Rightarrow 56=56 \\
\end{align}$
Since, LHS=RHS, therefore, our formula is correct.
Complete step-by-step answer:
Here we have to define the formula of ${{a}^{3}}-{{b}^{3}}$.
To get the formula of ${{a}^{3}}-{{b}^{3}}$, first of all, we have to derive the formula of ${{\left( a-b \right)}^{3}}$.
We know that ${{\left( a-b \right)}^{3}}=\left( a-b \right)\left( a-b \right)\left( a-b \right)$
By simplifying the RHS of above equation, we get,
$\begin{align}
& {{\left( a-b \right)}^{3}}=\left( a-b \right)\left( {{a}^{2}}-ab-ba+{{b}^{2}} \right) \\
& or\ {{\left( a-b \right)}^{3}}=\left( a-b \right)\left( {{a}^{2}}-2ab+{{b}^{2}} \right) \\
\end{align}$
By further simplifying the RHS of above equation, we get,
${{\left( a-b \right)}^{3}}={{a}^{3}}-2{{a}^{2}}b+{{b}^{2}}a-b{{a}^{2}}+2a{{b}^{2}}-{{b}^{3}}$
Therefore we get, ${{\left( a-b \right)}^{3}}={{a}^{3}}-{{b}^{3}}-3{{a}^{2}}b-3{{b}^{2}}a$.
We can also write the above equation as,
${{\left( a-b \right)}^{3}}={{a}^{3}}-{{b}^{3}}-3ab\left( a-b \right)$
Now by adding $3ab\left( a-b \right)$ on both sides of above equation, we get,
${{\left( a-b \right)}^{3}}+3ab\left( a-b \right)=\left( {{a}^{3}}-{{b}^{3}} \right)-3ab\left( a-b \right)+3ab\left( a-b \right)$
By cancelling the like terms from RHS, we get,
$\begin{align}
& {{\left( a-b \right)}^{3}}+3ab\left( a-b \right)=\left( {{a}^{3}}-{{b}^{3}} \right) \\
& or\ {{a}^{3}}-{{b}^{3}}={{\left( a-b \right)}^{3}}+3ab\left( a-b \right) \\
\end{align}$
By taking out (a - b) common from RHS, we get,
$\Rightarrow {{a}^{3}}-{{b}^{3}}=\left( a-b \right)\left[ {{\left( a-b \right)}^{2}}+3ab \right]$
As we know that ${{\left( a-b \right)}^{2}}={{a}^{2}}+{{b}^{2}}-2ab$, by applying it in above equation, we get,
$\Rightarrow {{a}^{3}}-{{b}^{3}}=\left( a-b \right)\left( {{a}^{2}}+{{b}^{2}}-2ab+3ab \right)$
Therefore we get, ${{a}^{3}}-{{b}^{3}}=\left( a-b \right)\left( {{a}^{2}}+{{b}^{2}}+ab \right)$
Hence we have found the formula for ${{a}^{3}}-{{b}^{3}}$which is equal to $\left( a-b \right)\left( {{a}^{2}}+{{b}^{2}}+ab \right)$.
Note: Here, apart from finding ${{\left( a-b \right)}^{3}}$by multiplying $\left( a-b \right)$ three times, students can directly use the formula of ${{\left( a-b \right)}^{3}}$, that is ${{\left( a-b \right)}^{3}}={{a}^{3}}-{{b}^{3}}-3ab\left( a-b \right)$.
Also students can cross check the formula by taking any value of a and b and satisfying them in formula as follows:
Let us take a = 4 and b = 2.
We have found that, ${{a}^{3}}-{{b}^{3}}=\left( a-b \right)\left( {{a}^{2}}+{{b}^{2}}+ab \right)$
By putting the values of a and b in above equation, we get,
$\Rightarrow {{\left( 4 \right)}^{3}}-{{\left( 2 \right)}^{3}}=\left( 4-2 \right)\left( {{\left( 4 \right)}^{2}}+{{\left( 2 \right)}^{2}}+4\times 2 \right)$
By simplifying the above equation, we get,
$\begin{align}
& \Rightarrow 64-8=\left( 2 \right)\left( 16+4+8 \right) \\
& \Rightarrow 56=2\left( 28 \right) \\
& \Rightarrow 56=56 \\
\end{align}$
Since, LHS=RHS, therefore, our formula is correct.
Recently Updated Pages
Express the following as a fraction and simplify a class 7 maths CBSE
The length and width of a rectangle are in ratio of class 7 maths CBSE
The ratio of the income to the expenditure of a family class 7 maths CBSE
How do you write 025 million in scientific notatio class 7 maths CBSE
How do you convert 295 meters per second to kilometers class 7 maths CBSE
Write the following in Roman numerals 25819 class 7 maths CBSE
Trending doubts
When people say No pun intended what does that mea class 8 english CBSE
In Indian rupees 1 trillion is equal to how many c class 8 maths CBSE
How many ounces are in 500 mL class 8 maths CBSE
Which king started the organization of the Kumbh fair class 8 social science CBSE
What is BLO What is the full form of BLO class 8 social science CBSE
Advantages and disadvantages of science